First collection of Habenaria pumila (Poepp.) (Orchidaceae) in Lanín National Park (Semiárida, 2022)
In this note the first collection of Habenaria pumila in the Lanín National Park is reported, a species cited for Patagonia Argentina in Nahuel Huapi National Park.
Keywords: Flora; Lanín National Park; Orchidaceae